Antibiotic synergist OM19r reverses aminoglycoside resistance in multidrug-resistant Escherichia coli - Cui, Qi; Yu, Han-Dong; Xu, Qi-Jun; Liu, Yue; Wang, Yu-Ting; Li, Peng-Hui; Kong, Ling-Cong; Zhang, Hai-Peng; Jiang, Xiu-Yun; Giuliodori, Anna Maria; Fabbretti, Attilio; He, Cheng-Guang; et al. (Frontiers in Microbiology, 2023)
Introduction The continued emergence and spread of multidrug-resistant (MDR) bacterial pathogens require a new strategy to improve the efficacy of existing antibiotics. Proline-rich antimicrobial peptides (PrAMPs) could also be used as antibacterial synergists due to their unique mechanism of action. Methods Utilizing a series of experiments on membrane permeability, In vitro protein synthesis, In vitro transcription and mRNA translation, to further elucidate the synergistic mechanism of OM19r combined with gentamicin. Results A proline-rich antimicrobial peptide OM19r was identified in this study and its efficacy against Escherichia coli B2 (E. coli B2) was evaluated on multiple aspects. OM19r increased antibacterial activity of gentamicin against multidrug-resistance E. coli B2 by 64 folds, when used in combination with aminoglycoside antibiotics. Mechanistically, OM19r induced change of inner membrane permeability and inhibited translational elongation of protein synthesis by entering to E. coli B2 via intimal transporter SbmA. OM19r also facilitated the accumulation of intracellular reactive oxygen species (ROS). In animal models, OM19r significantly improved the efficacy of gentamicin against E. coli B2. Discussion Our study reveals that OM19r combined with GEN had a strong synergistic inhibitory effect against multi-drug resistant E. coli B2. OM19r and GEN inhibited translation elongation and initiation, respectively, and ultimately affected the normal protein synthesis of bacteria. These findings provide a potential therapeutic option against multidrug-resistant E. coli.